Development of Fiqh Muamalah Learning in Sharia Economics Based on DSN-MUI Fatwas through the Maslahah Ath-Thufi Approach - Muhammad Rinaldo; Abd. Muthalib; Sumarni; Ashma Khairunnisa (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study analyzes the integration of Najm al-Din Ath-Thufi’s concept of maslahah within DSN-MUI fatwas and its implications for the teaching of fiqh muamalah. Using a qualitative normative-pedagogical approach, the study finds that DSN-MUI’s ijtihad is collective and integrative, employing bayānī, ta‘līlī, and istiṣlāḥī approaches. The principle of maslahah is substantively internalized in the fatwas through an orientation toward public interest, justice, and responsiveness to contemporary economic innovations, while remaining within the boundaries of definitive texts (nash qat‘i) and maqāṣid al-sharī‘ah. Pedagogically, this integration is relevant for developing contextual learning through a fatwa-based Problem-Based Learning (PBL) model, which bridges the gap between classical legal texts and modern economic practices. This study proposes an integrative framework linking maslahah, ijtihad methodology, and Islamic pedagogy.